Do shared traits create the same fates? Examining the link between morphological type and the biogeography of fungal and bacterial communities. (August 2020) - Daws, S. Caroline; Cline, Lauren A.; Rotenberry, John; Sadowsky, Michael J.; Staley, Christopher; Dalzell, Brent; Kennedy, Peter G.
Abstract: Although it has been commonly observed that fungi and bacteria differ in their regional biogeographic patterns, it is not well understood what traits contribute to these different distributions. Here, we evaluate how morphological type (i.e. unicellular or filamentous growth form) influences the biogeography of soil fungal and bacterial communities across not only Euclidean (i.e. geographic) distances, but also across gradients of climate and edaphic factors and plant community composition. Specifically, we assessed the decay in community similarity over distance (distance-decay relationship) for microbes with unicellular and filamentous morphology in both fungi and bacteria across 40 ecologically diverse sampling sites in Minnesota, USA. Overall, we found that while distance-decay relationships were similar in fungal and bacterial communities over Euclidean distances, there were important differences among morphological groups of fungi and bacteria across gradients of environmental and plant community similarity. Specifically, the distance-decay relationship of unicellular fungi and unicellular bacteria were indistinguishable across environmental similarity. However, as plant community similarity decreased, only filamentous fungi and unicellular bacteria differed significantly in the strength of their distance-decay relationships. Like analyses of other study systems, we also found that pH explained much of the variance in community composition across microbial domains and morphological types and that plant community diversity was more closely correlated with fungal diversity than with bacterial diversity. Collectively, our results suggest that specific ecological traits such as morphological type along with microbial domain are key factors shaping the biogeography of microbial communities. Graphical abstract: Image 1